PENERAPAN MEDIA FLASH CARD DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DI KELAS I SDN 14/I SUNGAI BAUNG - Argi Eko Siswanto; Anisa Amini; Vika Notalia Isa; Mayang Sari; Dastrinelli (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2023)
This study aims to explore and apply flash card media as an effective tool in improving early reading skills in class I SDN 14/I Sungai Baung. The research was conducted by involving 30 class IA students as research subjects. The method used was classroom action research consisting of four cycles, with each cycle involving planning, action, observation, and reflection stages. The results of the study show that consistent and directed application of flash card media can improve students' initial reading skills in class IA. Each research cycle resulted in a significant increase in students' reading ability. In addition, student participation and involvement in the learning process also increases with the use of flash card media. In addition, the results of this study also contribute to the development of varied and innovative learning methods at the elementary education level.